2005
DOI: 10.1136/emj.2004.014712
|View full text |Cite
|
Sign up to set email alerts
|

Rate of metoclopramide infusion affects the severity and incidence of akathisia

Abstract: Objective: To investigate the effect of the rate of metoclopramide infusion on akathisia incidence, severity, onset of symptoms, and duration in patients with headache, and/or nausea/vomiting in the emergency department (ED) setting. Methods: Prospective, double blind, randomised clinical study comparing two rates of intravenous infusion of metoclopramide over a period of six months at a tertiary university hospital ED. Results: A total of 300 patients presented to the ED met the inclusion criteria: 151 (50.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 19 publications
(14 reference statements)
2
37
1
3
Order By: Relevance
“…of metoclopramide does not result in additional efficacy in the ED setting (10). Also, metoclopramide given as an infusion over 15 min is less likely to cause akathisia than if the same dose is given as a bolus over 2 min (5.8% vs. 24.7%, respectively; p Ͻ 0.001) (43). This observation is replicated in another study in patients with headache that reported a 78% relative risk reduction of akathisia with an infusion over 15 min (44).…”
Section: Prochlorperazine and Metoclopramidementioning
confidence: 81%
“…of metoclopramide does not result in additional efficacy in the ED setting (10). Also, metoclopramide given as an infusion over 15 min is less likely to cause akathisia than if the same dose is given as a bolus over 2 min (5.8% vs. 24.7%, respectively; p Ͻ 0.001) (43). This observation is replicated in another study in patients with headache that reported a 78% relative risk reduction of akathisia with an infusion over 15 min (44).…”
Section: Prochlorperazine and Metoclopramidementioning
confidence: 81%
“…3,8,9 A recent study found that when metoclopramide was administered over 15 minutes, the severity and incidence of metoclopramide-induced akathisia was reduced compared with administration over two minutes. 19 If metoclopramide is administered rapidly, the patient may have anxiety, restlessness, and/or drowsiness. During and after administration, the patient should have vital signs and mental status monitored.…”
Section: Guidelines For Administrationmentioning
confidence: 99%
“…Se ha reportado que la incidencia y severidad de acatisia está relacionada a la velocidad de infusión de la metoclopramida parenteral (16,17). Tres estudios clínicos aleatorios y doble ciego concluyeron que infusiones lentas de metoclopramida (por alrededor de quince minutos) eran una estrategia efectiva para reducir la incidencia y severidad de la acatisia (1,17,18). En nuestro caso la administración de metoclopramida se dio en infusiones rápidas lo que aumentó el riesgo de aparición de acatisia.…”
Section: Rev Neuropsiquiatr 78 (1) 2015unclassified
“…La Administración de Alimentos y Medicamentos de los Estados Unidos de América ha limitado sus indicaciones a la gastroparesia diabética, al reflujo gastroesofágico, a procedimientos de radiografía gastrointestinal e intubación intestinal, y a Rev Neuropsiquiatr 78 (1), 2015.…”
Section: Introductionunclassified
See 1 more Smart Citation